Anesthesia for Percutaneous Pulmonary Valve Implantation: A Case Series. (July 2018) - Arboleda Salazar, Rafael; Heggie, Jane; Wolski, Piotr; Horlick, Eric; Osten, Mark; Meineri, Massimiliano
Abstract : BACKGROUND: Twenty percent of patients born with congenital heart disease present with right ventricular outflow tract abnormalities. These patients require multiple surgical procedures in their lifetime. Transcatheter pulmonary valve replacement (TPVR) has become a viable alternative to conventional pulmonary valve and right ventricular outflow tract surgery in pediatric and adult populations. In this retrospective review, we analyze the perioperative management of adult patients who underwent TPVR in our center. METHODS: The study consisted of a chart review of patients who underwent TPVR at Toronto General Hospital between 2006 and 2015. Information about preoperative assessment, intraoperative anesthetic management, and intra- and postprocedural complications was collected. Two types of percutaneous valves have been used for a conduit or valve size between 16 and 28 mm. These procedures are done via the femoral, jugular, or subclavian vein under general anesthesia. RESULTS: Seventy-nine adults (17–68 years of age) who underwent elective TPVR procedures were included. General anesthesia was used in all cases. Defibrillation was necessary in 1 case, and bradycardia was spontaneously resolved in another 1. Eighty-five percent were successfully extubated at the end of the procedure. Five patients required intraoperative inotropic support. Three patients presented self-resolved hemoptysis. Mechanical ventilation for >24 hours was necessary in 3 cases, 2 of which also required concomitant inotropic support. Four failed deployments and 1 case of persistent conduit stenosis were reported. Three patients required reintubation. All patients were discharged home. CONCLUSIONS: Patients undergoing TPVR represent a complex and heterogeneous population. General anesthesia with endotracheal intubation is preferred. Setup for urgent lung isolation and cardiac defibrillation should be considered. Postoperative monitoring and intensive care setting are required. Anesthesiologists with cardiac anesthesia training are probably better suited to manage these patients.